Bicarbonato de sodio como agente potenciador del efecto anestésico de la lidocaína en tejidos orales con presencia de infección en pacientes adultos. Revisión sistemática y Metaanálisis (2021)
The ste management and control of pain during dental care is a priority, in this sense, different authors have proposed the use of sodium bicarbonate as an agent capable of improving the anesthetic efficiency and effectiveness of LA in infected oral tissues.